KEPUTUSAN INVESTASI, PENDANAAN, DAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN RISIKO BISNIS SEBAGAI VARIABEL MEDIASI - Yuliani Yuliani; Isnurhadi Isnurhadi; Samadi W. Bakar (Jurnal Keuangan dan Perbankan, 2013)
This study aimed to analyze: the effect of investment decisions on firm value, the role of business risk as amediating effect investment decisions on firm value, the effect of financing decisions on firm value, the role ofbusiness risk as a mediating effect decisions financing on firm value, effect of dividend decisions on firm value,the role of business risk as a mediating effect dividend on firm value the effect of business risk on firm value.The research was conducted in the companies listed in Indonesia Stock Exchange (IDX). The observationperiod was 2009-2011. Based on the criteria population defined, the sampling method was census. The numberof analyzed samples were 18 companies. Data analysis was path analysis. The research findings were: theinvestment decisions could increase firm value, business risk did not have mediating effect on relationshipbetween investment decisions and firm value, the funding did not increase firm value, business risk as a fullmediation had an effect on relationship of funding and firm value, dividend decision did not have effect onfirm value, business risk did not have mediating effect on relationship between dividend decisions and firmvalue, business risk could increase firm value.